The synthesis of novel boronate esters and N-Heterocyclic carbene (NHC)-stabilized boronate esters: Spectroscopy, antimicrobial and antioxidant studies - Kilic, Ahmet; Savci, Ahmet; Alan, Yusuf; Beyazsakal, Levent (Elsevier Science Sa, 2020)
A new class of cheap, easily-synthesizable and modifiable boronate esters (B-1-B-3) and their corresponding N-Heterocyclic Carbene (NHC)-stabilized boronate esters (B-4-B-6) have been synthesized for the first time under toluene reflux using a Dean-Stark apparatus to remove the water by-product. All these newly synthesized boronate compounds were characterized using elemental analysis, and their probable structures were proposed based on H-1, C-13 and, B-11 NMR, FT-IR, UV-Vis spectral results and LC-MS/MS spectrometry. Antimicrobial activities of the boronate esters (B-1-B-3) and their corresponding N-Heterocyclic Carbene (NHC)-stabilized boronate esters (B-4-B-6) were investigated against 7 bacteria and 3 fungi. The boronate ester (B-1) showed the best antimicrobial activity. Besides, boronate ester (B1) with (NHC)-stabilized boronate esters (B-5 and B-6) showed better antibacterial activity than antibiotics drugs. It has been observed that the (NHC)-stabilized boronate ester (B-5) removes the scavenging effect of H2O2+DMSO and stabilizes plasmid DNA at the highest rate when applied alone. Addition, the boronate esters (B-1-B-3) and their corresponding N-Heterocyclic Carbene (NHC)-stabilized boronate esters (B-4-B-6) have been tested for the radical scavenging activity of antioxidants. They have meaningful antioxidant activity compared to reference compounds. The results show that 100 mL of the boronate esters had low activity according to standards when DPPH radical removal activities were compared to standards. (C) 2020 Elsevier B.V. All rights reserved.
Kilic, Ahmet/0000-0001-9073-4339
Keywords: Boronate esters; N-Heterocyclic carbene (NHC); Spectroscopy; Antimicrobial activity; Antioxidant properties